Directional hydrophone clusters reveal evasive responses of small cetaceans to disturbance at offshore windfarms - Graham, Isla; Gillespie, Douglas; Gkikopoulou, Kalliopi; Hastie, Gordon; Thompson, Paul (Zenodo, 2022)
Mitigation measures to disperse marine mammals prior to pile-driving include acoustic deterrent devices and piling soft starts, but their efficacy remains uncertain. W e developed a self-contained portable hydrophone cluster to detect small cetacean movements. Using an array of clusters within 10 km of foundation pile installations, we tested the hypothesis that harbour porpoises ( Phocoena phocoena ) respond to mitigation measures at offshore windfarm sites by moving away. During baseline periods, porpoise movements were evenly distributed in all directions. In contrast, animals showed significant directional movement away from sound sources during acoustic deterrent device use and piling soft starts. We demonstrate that porpoises respond to measures aimed to mitigate the most severe impacts of construction at offshore windfarms by swimming directly away from these sound sources. Portable directional hydrophone clusters now provide opportunities to characterise responses to disturbance sources across a broad suite of habitats and contexts. A full description of the data identifiers, R code and the data files required to repeat each analysis is provided in the text file: README_Graham_MEOW_cMMMP_Data_Packages.txt Data and code consist of the following 13 files/file packages. Graham_MEOW_cMMMP_construction_noise_data_2022-07-19.txt Graham_MEOW_cMMMP_construction_activity_data_2022-01-06.txt Graham_MEOW_cMMMP_directional_hydrophone_cluster_locations_and_distances_to_construction_data_2022-01-06.txt Graham_MEOW_cMMMP_R_code_to characterize_construction_noise_levels_2022-07-19.R Graham_MEOW_cMMMP_harbour_porpoise_click_data_2022-01-06.txt Graham_MEOW_cMMMP_R_code_to_process_and_analyse_harbour_porpoise_click_data_2022-07-19.R Depl1062.zip Depl1064.zip Depl1065.zip Depl1066.zip Depl1067.zip Depl1068.zip Depl1069.zip Funding provided by: Moray Offshore Wind Farm (East) Ltd.* Crossref Funder Registry ID: Award Number: